The Reinforcing and Inhibiting Factors of the Effectiveness Implementation on the Occupational Health and Safety Management Systems in Puskesmas Kota Semarang - Edison, Feramida Yuliya; Soesanto, Soesanto; Wijayanti, Yuni (Universitas Negeri Semarang, 2021)
Puskesmas was a workplace with a high risk to the health and safety of workers.The implementation of the occupational health and safety management systemat Puskesmas Kota Semarang has not been effective. This study aimed to analyzethe influence of reinforcing and inhibiting factors on the effectiveness of theimplementation of the occupational health and safety management system atPuskesmas. The type of this research was analytic observation using crosssectional. The population of this research was non-the occupational health andsafety officers who work in Puskesmas Kota Semarang. The sampling techniqueused was cluster random sampling. Bivariate analysis using chi-squareandmultivariate analysis using logistic regressions. The research result from 88respondents there was an influence between the occupational health and safetymanagement commitment, occupational health and safety managementsupervision, quality human resources, wage level and social security, data andinformation management, and implementation of the occupational health andsafety law enforcement on the effectiveness of the implementation of theoccupational health and safety management systems at Puskesmas, and there wasno influence on compliance variables against the las (behavior). The mostinfluential factors are data and information related to the occupational health andsafety OR (Exp B) 3,591. Suggestions that had given punishing and reviewing theoccupational health and safety written policy, the officers obey the occupationalhealth and safety directives and signs and play an active role in supervision, andfor the occupational health and safety team to evaluate the occupational healthand safety management and promotion once a month.